2007
DOI: 10.1016/j.mib.2007.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Role of polysaccharides in Pseudomonas aeruginosa biofilm development

Abstract: During the past decade, there has been a renewed interest in using P. aeruginosa as a model system for biofilm development and pathogenesis. Since the biofilm matrix represents a critical interface between the bacterium and the host or its environment, considerable effort has been expended to acquire a more complete understanding of the matrix composition. Here, we focus on recent developments regarding the roles of alginate, Psl, and Pel polysaccharides in the biofilm matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
398
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 514 publications
(408 citation statements)
references
References 33 publications
5
398
0
5
Order By: Relevance
“…P. aeruginosa produces at least three exopolysaccharides, namely, alginate, Psl, and Pel (32,33), which could influence the binding of Bac7 to the surface of the cells. Alginate is produced by a subset of strains that are often isolated from lungs of chronically colonized CF patients, and its overproduction is responsible for the mucoid phenotype of P. aeruginosa strains (32). Psl and Pel are often associated with nonmucoid strains and are necessary for biofilm formation (34).…”
Section: Mode Of Action Of Bac7(1-35) Against P Aeruginosamentioning
confidence: 99%
“…P. aeruginosa produces at least three exopolysaccharides, namely, alginate, Psl, and Pel (32,33), which could influence the binding of Bac7 to the surface of the cells. Alginate is produced by a subset of strains that are often isolated from lungs of chronically colonized CF patients, and its overproduction is responsible for the mucoid phenotype of P. aeruginosa strains (32). Psl and Pel are often associated with nonmucoid strains and are necessary for biofilm formation (34).…”
Section: Mode Of Action Of Bac7(1-35) Against P Aeruginosamentioning
confidence: 99%
“…The surface-dependent induction of algC expression correlated with stability of attachment, with cells that did not undergo algC upregulation demonstrating reduced ability to remain attached to the surface relative to that of cells with activated expression (33). While these findings suggested increased alginate production upon attachment, with alginate production contributing to biofilm resistance and being inversely linked to both flagellum-driven motility and twitching motility (48,139,165), it is now apparent that alginate is neither the major matrix polysaccharide nor required for biofilm development by nonmucoid P. aeruginosa strains, which are the first to colonize CF patients (121,144,167). Instead, recent chemical and genetic studies have demonstrated that the major polysaccharides produced by P. aeruginosa strains PAO1 and PA14 are Psl and Pel, with the roles of these two polysaccharides differing with respect to attachment and biofilm formation in a strain-specific manner.…”
Section: Figmentioning
confidence: 99%
“…14) At least three exopolysaccharides are produced by P. aeruginosa: alginate, Psl, and Pel. 14) Although it has been reported that ethanol enhances alginate synthesis in P. aeruginosa, 15) PAO1 produces little or no detectable alginate in vitro.…”
Section: )mentioning
confidence: 99%